2011
DOI: 10.4039/n11-034
|View full text |Cite
|
Sign up to set email alerts
|

Ants and subterranean Sternorrhyncha in a native grassland in east-central Alberta, Canada

Abstract: Little is known about the associations of ants (Hymenoptera: Formicidae) with subterranean aphids and mealybugs (Hemiptera: Sternorrhyncha: Aphididae and Pseudococcidae), particularly in Canadian grasslands. Knowledge of host plants for these sternorrhynchans is equally rare. We carried out a plant-based survey of ants and belowground aphids and mealybugs in a native fescue grassland in east-central Alberta, Canada. We found 23 species of ants, 12 of which (species of Lasius F., Myrmica Latreille, Tapinoma För… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, it is reported to occur in India in areas which experience temperatures that range from 0°C to 45°C (Sharma, 2007 ). What is remarkable is that it has been found in the Canadian prairies in Alberta on the roots of Artemisia frigida and Rosa arkansana in the nests of six species of ant (Newton et al., 2011 ). Two of these ant species are very common throughout the EU: yellow meadow ant Lasius flavus and black garden ant Lasius niger .…”
Section: Pest Categorisationmentioning
confidence: 99%
“…However, it is reported to occur in India in areas which experience temperatures that range from 0°C to 45°C (Sharma, 2007 ). What is remarkable is that it has been found in the Canadian prairies in Alberta on the roots of Artemisia frigida and Rosa arkansana in the nests of six species of ant (Newton et al., 2011 ). Two of these ant species are very common throughout the EU: yellow meadow ant Lasius flavus and black garden ant Lasius niger .…”
Section: Pest Categorisationmentioning
confidence: 99%
“…Rhagidiidae was the focus of revisions by Zacharda (Table 3), which included the description of 16 new species from Canada, but clearly much work remains to document this family fully. The putatively predatory family Strandtmanniidae was described by Zacharda (1979); it has been recorded from Alberta (Newton 2013) and New Brunswick, although not identified to named species. While little has changed since 1979 for the depauperate families Penthaleidae and Penthalodidae, the relatively high number of BINs for each suggests additional species remain to be identified.…”
Section: Superorder Acariformes: Order Trombidiformesmentioning
confidence: 99%
“…More restricted ecological surveys have been published for mites in forest canopies of the Pacific coast (Fagan et al 2006, Lindo and Winchester 2006, 2009), in soil and litter (e.g., St. John et al 2002, Déchêne and Buddle 2009, BehanPelletier and Kanashiro 2010, Sylvain and Buddle 2010, Walter and Latonas 2012, Newton 2013, Meehan and Turnbull 2018), peatlands (BehanPelletier and Bissett 1994, Barreto and Lindo 2018, McAdams et al 2018), in dung (Lindquist 1998), and on plants (Forest et al 1982, Beaulieu and Knee 2014), bumble bees (Haas et al in press), beetles (Lindquist and Wu 1991, Knee et al 2013), and birds (Galloway et al 2014, Knee and Galloway 2017b). For certain families or higher taxa of Acari, these publications represent a key source of information for species records in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Kozár et al (1989) identified several species of scale insects new to Canada based on brief collecting efforts in southern British Columbia. In a recent study of ant–sternorrhynch associations at a single grassland site in Alberta, two of the four species of Pseudococcidae found were newly recorded for Canada (Newton et al 2011). The number of available BINs (see Table 1), largely based on untargeted sampling by the Biodiversity Institute of Ontario (University of Guelph), has indicated that current knowledge greatly under-represents the true fauna of Psyllidae and Aleyrodidae if BIN diversity can be considered a good approximation of species diversity in these groups.…”
Section: Sternorrhynchamentioning
confidence: 99%